2018
DOI: 10.1111/1750-3841.14195
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Goat and Cow Milk Ratios on the Physicochemical, Rheological, and Sensory Properties of a Fresh Panela Cheese

Abstract: Fresh cheeses, Panela type, were manufactured from cow milk and with goat milk incorporation, constituting 4 blends of milks (G10:C90, G20:C80, G30:C70, G40:C60, v/v). The cheeses were analyzed to determine the effect of the different goat milk ratios on the physicochemical, textural, rheological, and sensory properties over 15 d of storage. Significant differences in protein (14.6% to 18.5%), fat (13.0% to 19.4%), and moisture contents (51.7% to 61.3%), pH (6.38 to 6.67), color (L > 64.4, a > 1.06, b > 5.14),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
10
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 32 publications
6
10
2
Order By: Relevance
“…This corroborates different studies reporting that GM is similar to CM in basic composition [14]. However, other investigations have highlighted contradictory variations in fat content [12,28,30,37]. Some studies have also observed a decrease in protein content [28,30,37], moisture, and salt [30], while others [12] have reported an increase in moisture and fat-in-dry matter (FDM) contents and no significant effects on protein, moisture-in non-fat-substance (MNFS), and salt.…”
Section: Cheese Proximate Compositionsupporting
confidence: 91%
See 2 more Smart Citations
“…This corroborates different studies reporting that GM is similar to CM in basic composition [14]. However, other investigations have highlighted contradictory variations in fat content [12,28,30,37]. Some studies have also observed a decrease in protein content [28,30,37], moisture, and salt [30], while others [12] have reported an increase in moisture and fat-in-dry matter (FDM) contents and no significant effects on protein, moisture-in non-fat-substance (MNFS), and salt.…”
Section: Cheese Proximate Compositionsupporting
confidence: 91%
“…However, other investigations have highlighted contradictory variations in fat content [12,28,30,37]. Some studies have also observed a decrease in protein content [28,30,37], moisture, and salt [30], while others [12] have reported an increase in moisture and fat-in-dry matter (FDM) contents and no significant effects on protein, moisture-in non-fat-substance (MNFS), and salt. According to Ramírez-López and Vélez-Ruiz [28], no differences were observed for lactose and non-fat solids.…”
Section: Cheese Proximate Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…For flavor evaluation, a trained descriptive sensory panel ( n = 20; 15 females and five males, ages 22–40 years) evaluated the milk knot in triplicate using a milk knot flavor lexicon (creamy aroma, sweet, oxidized aroma, whey, sour aroma, milky rancid, and waxy; Boris et al, 2018; Hailu et al, 2018; Hickey et al, 2018; Jo, Benoist, Ameerally, & Drake, 2018; Ramírez‐López & Vélez‐Ruiz, 2018). Panelists were trained and used the sensory intensity descriptors in Table S1 for experimental samples as described.…”
Section: Methodsmentioning
confidence: 99%
“…Hailu et al (2018) conducted training in four basic sensory methods of descriptive vocabulary (aroma, appearance, texture, and taste), selecting 10 well‐trained team members to do descriptive sensory analysis, the descriptive vocabulary of selection is silage, moldy, watery, firmness, sweet, salty, and sour. Ramírez‐López and Vélez‐Ruiz (2018) used the technique of “quantitative descriptive analysis” (QDA) to evaluate the texture of milk knot after processing 24 hr. The relationship between sensory and instrumental perception of the milk knot texture was determined by a 5‐point scale (from “zero” to “extreme”) which represents the perceived intensity of each texture attribute in conjunction with a description of the sensory analysis.…”
Section: Introductionmentioning
confidence: 99%